PENGEMBANGAN INSTRUMEN ASESMEN OPEN ENDED QUESTION PADA KURIKULUM MERDEKA UNTUK MENGUKUR KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK - Rifani, Rini; Prasetyo, Teguh; Indra, Syukri; Hayu, Wiworo Retnadi Rias (Jurnal Penjaminan Mutu, 2025)
This study aims to describe the development and analyze the criteria for an Open-ended-question-based assessment instrument within the Merdeka Curriculum, designed to measure the creative thinking skills of 4th-grade elementary school students. The research adopts a nine-step instrument development model: defining the instrument's purpose, determining the scope of material, developing item indicators, constructing the instrument items, conducting content validity, revising the instrument, pilot testing, analyzing the trial results, and assembling the final instrument. The content validity analysis using Aiken's V index, conducted by three validators, indicated that four assessment items had moderate validity and eight had high validity. Large-scale product testing produced the following results: (1) validity tests of 10 questions showed all questions were valid, (2) the instrument items were reliable with a Cronbach's Alpha of 0.822, indicating very high reliability, (3) difficulty index analysis revealed eight items were of medium difficulty and two items were easy, and (4) discrimination index analysis showed two items were moderately good, six items were good, and two items were perfect. Thus, it can be concluded that the developed assessment instrument is suitable for use.